Bisphosphonates for delivering drugs to bone. (10th April 2021) - Sun, Shuting; Tao, Jianguo; Sedghizadeh, Parish P.; Cherian, Philip; Junka, Adam F.; Sodagar, Esmat; Xing, Lianping; Boeckman, Robert K.; Srinivasan, Venkatesan; Yao, Zhenqiang; Boyce, Brendan F.; Lipe, Brea; et al.
Abstract : Advances in the design of potential bone‐selective drugs for the treatment of various bone‐related diseases are creating exciting new directions for multiple unmet medical needs. For bone‐related cancers, off‐target/non‐bone toxicities with current drugs represent a significant barrier to the quality of life of affected patients. For bone infections and osteomyelitis, bacterial biofilms on infected bones limit the efficacy of antibiotics because it is hard to access the bacteria with current approaches. Promising new experimental approaches to therapy, based on bone‐targeting of drugs, have been used in animal models of these conditions and demonstrate improved efficacy and safety. The success of these drug‐design strategies bodes well for the development of therapies with improved efficacy for the treatment of diseases affecting the skeleton. LINKED ARTICLES: This article is part of a themed issue on The molecular pharmacology of bone and cancer‐related bone diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.9/issuetoc